2009
DOI: 10.3748/wjg.15.4143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of the profibrogenic effects of endothelin-1 in pancreatic stellate cells

Abstract: AIM:To gain molecular insights into the expression and functions of endothelin-1 (ET-1) in pancreatic stellate cells (PSC). METHODS:PSCs were isolated from rat pancreas tissue, cultured, and stimulated with ET-1 or other extracellular mediators. Cell proliferation was assessed by measuring the incorporation of 5-bromo-2'-deoxyuridine into DNA and cell migration was studied in a transwell chamber assay. Gene expression at the level of mRNA was quantified by real-time polymerase chain reaction. Expression and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In relation to the PSCs' property of an excessive production of type-I collagen, they are regarded to be the major source of fibrosis in CP. 11,12,32 In result of the use of a nonspecific ET-1 antagonist (bosentan), Jonitz et al 11 observed an inhibition of the PSCs growth. In the in vitro studies, the use of bosentan resulted in a reduction in collagen synthesis by PSCs, as well as in the decrease in the ET-1 mRNA expression in these cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In relation to the PSCs' property of an excessive production of type-I collagen, they are regarded to be the major source of fibrosis in CP. 11,12,32 In result of the use of a nonspecific ET-1 antagonist (bosentan), Jonitz et al 11 observed an inhibition of the PSCs growth. In the in vitro studies, the use of bosentan resulted in a reduction in collagen synthesis by PSCs, as well as in the decrease in the ET-1 mRNA expression in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…33 Therefore, it has been concluded that the existing relationship between PSCs and the ET-1 and its receptors increases the inflammation and accelerates the pancreatic fibrosis. 11 Owing to strong vasoconstrictor properties of ET-1, high level of this peptide contributes to local tissue ischemia, leading to the pancreas damage. 32 This correlation is confirmed by the present study, where the tissue with a strong ET-1 expression was characterized by a significant stroma reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of knowledge about the variety of factors that are known to be upregulated during pancreatic injury/necroinflammation, researchers have assessed the response of cultured PSCs to a wide range of potential activators including (Table 16.1): (i) proinflammatory cytokines, chemokines, and growth factors, e.g., interleukins, TNFα, CXCR12, TGFβ, connective tissue growth factor (CTGF), and platelet derived growth factor (PDGF); (ii) alcohol and its metabolites acetaldehyde and fatty acid ethyl ester (FAEE) (given the known role of alcohol in pancreatitis) [31]; (iii) endotoxin (lipopolysaccharide, LPS) [32]; in view of the known association between alcohol abuse and endotoxemia [33] and the positive correlation between circulating LPS levels and severity of pancreatitis [34]; (iv) oxidant stress (which occurs during both acute and chronic pancreatitis) [35,36]; (v) increased pancreatic pressure (secondary to the compartment syndrome in chronic pancreatitis) [37]; hyperglycemia (since diabetes is a known association of chronic pancreatitis) [38]; (vi) angiotensin (given the upregulation of the reninangiotensin system during pancreatitis) [39]. More factors are added to this list everyday with some of the more recent factors including endothelin 1 (a vasoconstrictor secreted by endothelial cells) [40]; cyclooxygenase 2 (COX-2, which catalyzes conversion of arachidonic acid to prostaglandin) [41]; pigment epithelium derived factor, a non-inhibitory member of the serine protease inhibitor gene family [42]; galectin 1 (a beta galactoside-binding lectin) [43]; hypoxia, usually a consequence of vasoconstriction and inadequate oxygenation in dense fibrosis [44]; proteases (prematurely activated within the gland during pancreatitis) [45]; and the hemostatic protein fibrinogen [46]. Upon exposure to the previous factors in vitro, PSC activation has usually been assessed by various parameters, the most common being loss of vitamin A, α-sma expression, proliferation, synthesis of ECM proteins and MMPs, contractility, migration, and cytokine release.…”
Section: Activation Of Pscsmentioning
confidence: 95%
“…Cellular proteins received from equal numbers of cells were separated by SDS-polyacrylamide gel electrophoresis (10%-12% gels, depending on the experimental requirements) and transferred onto PVDF membrane by semidry blotting. After blotting, the filters were blocked and processed by incubation with the indicated primary antibody as previously described [20,21] . The secondary antibody was IRDye ® 800CW conjugated goat anti-mouse IgG and goat anti-rabbit IgG, respectively.…”
Section: Immunoblottingmentioning
confidence: 99%